Artificial Intelligence and Entrepreneurship: A Call for Research to Prospect and Establish the Scholarly AI Frontiers - Obschonka, Martin; Grégoire, Denis A.; Nikolaev, Boris; Ooms, Frédéric; Lévesque, Moren; Pollack, Jeffrey M.; Behrend, Tara S. (Entrepreneurship Theory and Practice, 2025)
Entrepreneurship has entered a new era shaped by artificial intelligence (AI), demanding accelerated scholarly advances to keep pace with this transformative technology—yet this demands that academics bridge the gap between the AI revolution’s ambiguities and meaningful scholarly contributions. To motivate and guide future research on AI’s transformative role in entrepreneurship, we introduce an ongoing special issue in Entrepreneurship Theory and Practice ( ETP ) and outline multiple compelling opportunities for future research. Unlike typical editorials, we offer a prospective vision—rather than retrospective, after the articles have been accepted and published—at this project’s outset, to empower the field to prospect and establish new scholarly foundations in the relatively uncharted world of AI in the domain of entrepreneurship. Accordingly, we highlight the “AI PEN” ( P rospecting and E stablishing N exus) as a desirable research approach to advance this literature going forward. We hope, and anticipate, that our invitation to submit proposals to this special issue facilitates novel empirical as well as theory-focused contributions to the literature.